Health-Related Quality of Life in Patients With Alpha-1 Antitrypsin Deficency: a Cross Sectional Study - Redondo, MT (2017)
Background: Measures of health related quality of life (HRQoL) in patients with α1-antitrypsin deficiency (AATD) can help to determine the impact of the disease and provide an important insight into the intervention outcomes. There is few data regarding this issue in the literature. The aim of this study is to assess the relationship between HRQoL and gender, functional parameters and history of hospitalizations in patients with AATD. Methods: This is a cross-sectional study of 26 patients with severe AATD recruited in the pulmonology outpatient clinic at a tertiary care medical center. Social-demographic, clinical and functional parameters were recorded and HRQoL was assessed with the Portuguese version of the medical outcome study short form-36 (SF-36) self-administered questionnaire. Results: Older patients, females and patients with at least one hospitalization in the previous year due to respiratory disease had statistical lower scores in some dimensions of the SF-36 questionnaire. Superior FEV1 and higher distance mark in the 6-min walking test distance influenced positively several dimensions of the questionnaire. Higher scores in the mMRC scale influenced negatively the HRQoL. Conclusions: These data suggests that older and female patients with AATD have worse HRQoL. Hospitalizations and functional markers of respiratory disease progression influenced negatively the HRQoL, suggesting that the SF-36 questionnaire could be useful as an outcome for AATD patients with lung involvement.